THE EFFECT OF WORK LIFE BALANCE AND COMPENSATION ON TURNOVER INTENTION WITH JOB STRESS AS A MEDIATION VARIABLE IN PT XYZ'S MILLENNIAL EMPLOYEES - Ferzanita, Sharfina (Dynamic Management Journal, 2023)
Tujuan penelitian ini untuk mengetahui pengaruh work life balance terhadap turnover intention, mengetahui pengaruh kompensasi terhadap turnover intention, mengetahui pengaruh work life balance terhadap turnover intention yang dimediasi oleh stres kerja, mengetahui pengaruh kompensasi terhadap turnover intention yang dimediasi oleh stres kerja, serta mengetahui pengaruh stres kerja terhadap turnover intention. Penelitian ini menggunakan metode kuantitatif. Jumlah sampel terdiri dari 32 karyawan PT XYZ menggunakan teknik sampling sensus dimana seluruh anggota populasi dijadikan sebagai sampel. Pengolahan data pada penelitian ini menggunakan aplikasi SmartPLS 3.0 dengan metode Structural Equation Model (SEM) Partial Least Square (PLS). Hasil penelitian ini menunjukkan bahwa (1) work life balance berpengaruh positif dan signifikan terhadap turnover intention, (2) kompensasi tidak berpengaruh dan tidak signifikan terhadap turnover intention, (3) work life balance berpengaruh positif dan signifikan terhadap turnover intention yang dimediasi oleh stres kerja, (4) kompensasi berpengaruh positif dan signifikan terhadap turnover intention yang dimediasi oleh stres kerja, dan (5) stres kerja berpengaruh positif dan signifikan terhadap turnover intention.The purpose of this research is to determine the influence of work life balance on turnover intention, determine the influence of compensation on turnover intention, determine the influence of work life balance on turnover intention which is mediated by work stress, determine the influence of compensation on turnover intention which is mediated by work stress, and determine the influence of stress. work on turnover intention. This research uses quantitative methods. The total sample consisted of 32 PT XYZ employees using census sampling techniques where all members of the population were used as samples. Data processing in this research used the SmartPLS 3.0 application with the Structural Equation Model (SEM) Partial Least Square (PLS) method. The results of this reserach found that (1) work-life balance has a positive and significant effect on turnover intention, (2) compensation has no effect and is not significant on turnover intention, (3) work-life balance has a positive and significant effect on turnover intention mediated by jobstress, (4) compensation has a positive and significant effect on turnover intention mediated by jobstress, and (5) jobstress has a positive and significant effect on turnover intention.